1981
DOI: 10.1002/jez.1402160317
|View full text |Cite
|
Sign up to set email alerts
|

Drugs that block smooth muscle contraction inhibit in vivo ovulation in hamsters

Abstract: We have demonstrated previously that smooth muscle cells (SMC) in the base of hamster follicles contract minutes before ovulation. The contraction of these cells correlates well in time with the development of a constriction in the base of the follicle. The purpose of this study was to determine whether contraction of SMC (1) produces this constriction and (2) is necessary for ovulation. We treated preovulatory hamster ovaries with six classes of drugs (lanthanides, calcium antagonists, local anesthetics, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that these cells contract prior to ovulation [5,25,26]. This contraction is correlated with the development of a V-shaped constriction in the basis of the Graafian follicle, which is required for ovulation [27]. Self et al [28] showed in the hamster that the theca externa is a functional contractile system that responds to a Ca2+ influx.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that these cells contract prior to ovulation [5,25,26]. This contraction is correlated with the development of a V-shaped constriction in the basis of the Graafian follicle, which is required for ovulation [27]. Self et al [28] showed in the hamster that the theca externa is a functional contractile system that responds to a Ca2+ influx.…”
Section: Discussionmentioning
confidence: 97%
“…Espey, 1980). Other prostaglandininduced phenomena that have been implicated in follicular rupture include the mobilization of fibroblasts (Espey et al, 1981) and follicular contractions (Martin and Talbot, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…That this event plays a role in ovulation has been suggested by Martin & Talbot (1981b), who demonstrated that ovulation in hamsters could be inhibited by a variety of drugs known to inhibit smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 90%